Identifikasi Penggunaan Alat Permainan Edukatif Dalam Mengembangkan Kognitif Anak Usia 5-6 Tahun di Tk Se-Kecamatan Labuhan Haji Tahun 2021 - Fahruddin Fahruddin; Nurhasanah Nurhasanah; Baik Nilawati Astini; Ghina Sonia (Indonesian Publication Center, 2022)
This study aims to determine which educational game tools (APE) are used, dominantly used and appropriate to use in developing the cognitive development of children aged 5-6 years in Kindergartens throughout Labuhan Haji District in 2021. The type of research used is survey research. The population in kindergartens in Labuhan Haji District is 125 teachers with a sample of 33 teachers. The sampling technique used is Simple Random Sampling. Data collection methods in this study are questionnaires, interviews, and documentation methods. By analyzing the data descriptively quantitatively. The research results obtained from 30 APE. The APE used in developing the cognitive development of children aged 5-6 years is 30 APE or 100%. The dominant APE used in developing the cognitive development of children aged 5-6 years is 21 APE or 70% and the APE that is suitable for use in developing the cognitive development of children aged 5-6 years is 15 APE or 50%.